Prek ciljev aerobne vadbe do zdravega življenjskega sloga med šolanjem na daljavo - Maver, Petra (Šport (Ljubljana), 2021)
The article presents an example of on line teaching, utilising an authentic approach at subject Sport in 9th grade. In the course of six weeks students were connecting practical and theoretical contents on the subject of general conditioning to realise goals, leading to developing a healthy lifestyle and aerobic endurance. The final product of their work was an individual exercise program which had to show that the student understood and was able to connect the contents, while being useful to the student. The product of their work was graded according to critieria which were set in advance.
Keywords: checking for understanding; COVID-19; distance learning; epidemic; epidemije; grading; individualni načrt vadbe; ocenjevanje; on line teaching; osnovne šole; physical education; pouk na daljavo; preverjanje; primary school; sport; šolanje na daljavo; šport; športna vzgoja